Comorbidities, anthropometric, demographic, and lifestyle risk factors for ulnar neuropathy at the elbow: A case control study. Issue 4 (7th November 2020) - Mondelli, Mauro; Mattioli, Stefano; Vinciguerra, Claudia; Ciaramitaro, Palma; Aretini, Alessandro; Greco, Giuseppe; Sicurelli, Francesco; Giorgi, Stefano; Curti, Stefania
Abstract: We performed a prospective multicenter case‐control study to explore the association between ulnar neuropathy at elbow (UNE) and body and elbow anthropometric measures, demographic and lifestyle factors, and comorbidities. Cases and controls were consecutively enrolled among subjects admitted to four electromyography labs. UNE diagnosis was made on clinical and neurographic findings. The control group included all other subjects without signs/symptoms of ulnar neuropathy and with normal ulnar nerve neurography. Anthropometric measurements included weight, height, waist, hip circumferences, and external measures of elbow using a caliper. The participants filled in a self‐administered questionnaire on personal characteristics, lifestyle factors, and medical history. We estimated odds ratios (ORs) and 95% confidence intervals (CIs) by fitting unconditional logistic regression models adjusted by center and education level. We enrolled 220 cases (males 61.8%; mean age 51.7 years) and 460 controls (47.4% males; mean age 47.8 years). At multivariable analysis, UNE was associated to male gender (OR = 2.4, 95%CI = 1.6‐3.7), smoking habits (>25 pack‐years (OR = 2.3, 95%CI = 1.3‐4.1), body mass index (OR = 1.05, 95%CI 1.01‐1.10), polyneuropathies (OR = 4.1, 95%CI 1.5‐11.5), and leaning with flexed elbow on a table/desk (OR = 1.5, 95%CI 1.0‐2.2). Cubital groove width (CGW) turned out to be negatively associated with UNE (OR = 0.80, 95%CI = 0.74‐0.85). Our study suggests that some personal factors especially anthropometric measures of the elbow may play a role in UNE pathogenesis as the measures of wrist in CTS. We demonstrated that for each millimeter of smaller CGW the risk of idiopathic UNE increases of 25%.